Impulsivity and Entrepreneurship During and Post-Pandemic Crises - Games, Donard; Hidayat, Danny; Sari, Dessy Kurnia; Albatati, Bader (RSF Conference Series: Business, Management and Social Sciences, 2022)
There is little research that examines the consequences of impulsivity on entrepreneurship including entrepreneurial psychological aspects. The objective of this research is to examine the possible relationships between impulsivity and entrepreneurship. We offer entrepreneurial fear of failure and entrepreneurial well-being as constructs that can capture the essence of entrepreneurship related to impulsivity. COVID-19 pandemic and post pandemic crises have caused a shift on how entrepreneurs perceive their entrepreneurial behavior and well-being. We use an integrated review to analyse the relationship and provide some propositions for future research by interpreting previous research and following them up with new insights. While impulsive behaviors are frequently regarded as irrational and emotional, quick decision making, we will provide a greater understanding of this issue.